Histories on econometrics - Boumans, Marcel; Dupont-Kieffer, Ariane; Qin, Duo. (Durham Duke University Press, 2011)
"These essays consider applied research and methodologies in context and connect the history of econometrics to contemporary developments in related disciplines and technologies. Analyzing the practice of econometrics around the world since its introduction in the 1920s, contributors examine the relationship between sociology and welfare in Italian econometrics, the extraordinary investment in macroeconometric models and input-output models in Japan, practices of econometrics in relation to computation and philosophy, and the recognition of unusual methodological stances in both theoretical and applied work." [Publisher's description].
Foreword / Mary S. Morgan -- A history of histories of econometrics / Marcel Boumans and Ariane Dupont-Kieffer -- Econometrics and psychometrics : rivers out of biometry / John Aldrich -- The fellowship of econometrics : selection and diverging views in the province of mathematical economics, from the 1930s to the 1950s / Francisco Louçã and Sofia Terlica -- Econometrics and the computer : love or a marriage of convenience? / Charles G. Renfro -- Ragnar Frisch and the probability approach / Olav Bjerkholt and Ariane Dupont-Kieffer -- Ta-Chung Liu's exploratory econometrics / Hsiang-Ke Chao and Chao-Hsi Huang -- Tobin as an econometrician / Robert W. Dimand -- A history of Japanese developments in econometrics / Aiko Ikeo -- Corrado Gini (1884-1965) : the leading figure of the Italian Group in the Econometric Society / Daniela Parisi -- The introduction of the Cobb-Douglas Regression and is adoption by agricultural economists / Jeff E. Biddle -- The early years of panel data econometrics / Ariane Dupont-Kieffer and Alain Pirotte -- The Phillips Curve from the perspective of the history of econometrics / Duo Qin -- Reconceiving quality : political economy and the rise of hedonic price indexes / Thomas A. Stapleford.
Keywords: Econometrics -- History; Economics -- History